Prosecutions against people who cultivate and produce cannabis derivatives in Argentina (2010-2020) (Delito y Sociedad, 2026)
This article analyzes how the judicial system processes cases related to practices associated with the cultivation and/or production of cannabis derivatives. The analysis is based on interviews with people who were tried for these crimes between 2010 and 2020, their relatives and/or lawyers. The people contacted for this study were listed on databases compiled by cannabis organizations that recorded these types of cases during the period studied, to highlight the persecution of cannabis users and growers. The interest of this work lies in the fact that the information published by state agencies is limited to the initial stage of the process and does not provide insight into the treatment given to these cases nor the resolutions reached in these types of proceedings. The research reveals that the way the seized material is interpreted, the lack of questioning of police actions, and flaws in the forensic reports allow these cases to advance through the judicial system, even to the trial stage. Then, as people prove they are users and/or «solidary growers», the more serious legal typifications are dropped, so a low percentage of convictions is achieved.
Keywords: drugs; cannabis; cultivation; law enforcement; judicial practices